STRATEGI DINAS PARIWISATA DAN KEBUDAYAAN DALAM PENGELOLAAN PARIWISATA DI KABUPATEN PANGANDARAN TAHUN 2020-2021 - Nisa Azizah; Nandang Alamsah Deliarnoor; Novie Indrawati Sagita (Jurnal Ilmiah Wahana Bhakti Praja, 2023)
Problems in the field show that the strategy for developing and structuring tourism areas carried out by the Regional Government of Pangandaran Regency is still not effective. This is shown through the arrangement of tours that are carried out more specifically the most favorite tourist destinations. Where the street vendors who are now in the core zone have been moved to the back, but because the transfer of traders does not follow the path of tourists, the interaction of traders with tourists is difficult. This study uses a descriptive method with a qualitative approach, with data collection techniques through literature and field studies which include interviews, observation and documentation with informants from both the Tourism and Culture Office internal, the management of tourist attractions, visitors to tourist attractions, community leaders, and as well as the people in Panngandaran Regency. Data analysis techniques are carried out through data collection, data presentation and drawing conclusions. The results of this study indicate that the strategy of the Department of Tourism and Culture in managing tourism in Pangandaran Regency in 2020-2021 is still not effective, this can be seen from the following three dimensions; (1) The strategy implemented by the Tourism and Culture Office in managing tourism in Pangandaran Regency for 2020-2021 has not met the first indicator, namely strategy formulation. (2) The strategy implemented by the Tourism and Culture Office in managing tourism in Pangandaran Regency for 2020-2021 has not met the second indicator, namely the implementation of the strategy. (3) The strategy implemented by the Tourism and Culture Office in managing tourism in Pangandaran Regency for 2020-2021 has not fulfilled the third indicator, namely the assessment of the strategy. Key words; Strategy, Department of Tourism and Culture, Tourism Management